Suppose that 6 is one of the roots of quadratic equation x 2 − 2 x + a = 0 . What is the other root?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I'm adopted 96
6 2 − 2 ( 6 ) + a = 0 a = − 2 4 x 2 − 2 x − 2 4 = 0 ( x + 4 ) ( x − 6 ) = 0 So x = − 4 or x = 6
The other root is -4
I understood the steps but it is like substituting x at its position again
plug in 6 into x, and solve for a we get that a=-24. Plug in this value of a into the original equation and solve for x we get x=-4 or 6. Therefore -4 is the answer
From the Gerenal equation of quadratic equation ax^2+bx +c =0 From the rules in finding the roots in quadratic equation... The sum of two roots r1 + r2 =-b/a and the products of two roots r1.r2=c/a So you have a given equation of quadratic equation which is x^2-2x +a =0 Your a=1;b=-2; c=a one root is given let say that is r1=6 to find the 2nd root. So r1 + r2 =-b/a 6 + r2 =-(-2)/1 r2= 2-6 r2=-4 ans. To find a=>c Take the product of the roots r1.r2=c/a 6.-4=c=>a a=-24 So the equation would be x^2 -2x -24=0 To check by factoring the equation you have( x-6)(×+4)=0 X1=6 which is the first root X2=-4 which is the second root.
we know that x^2+2x+1 has a line of symmetry at x=1 and that changing the last coefficient won't change the line of symmetry so if one root of x^2+2x+a is 6 then the other is an equal distance from 1 and since 6-1=5 then the other root is 1-5 which is -4
We know that:
x 1 + x 2 = a − b And we have:
x 1 = 6 b = − 2 a = 1 So:
x 2 = a − b − x 1 x 2 = 1 2 − 6 x 2 = − 4
(x-6)(x+4) = 0; So, x - 6 = 0 & x + 4=0; x=6 & x=-4
First, use 6 to substitute x and find the value of a
Then 6^2-2x6+a=0
36-12+a=0
24+a=0
a=-24
Use the quadratic formula to find the other root
......(Can't type radicals)
The other root is -4
(6)^2 - 2 (6) + a = 0
a = - 24
x^2 - 2 x - 24 = 0
(x + 4)(x - 6) = 0
x = -4 or x = 6
The other root is -4
Knowing that 6 is one of the roots, you can plug it into the equation and solve for a first. After that, solve this quadratic equation.
Problem Loading...
Note Loading...
Set Loading...
By Vieta's, the sum of the roots is 2 . Since 6 is one of the roots, the other one is 2 − 6 = − 4